Perceptions of COVID-19 during and after the Omicron outbreak among healthcare personnel in Indonesia - Maruf, Mohammad Ainul; Weng, Yi-Hao; Chiu, Ya-Wen; Chiou, Hung-Yi (Frontiers in Public Health, 2024)
The COVID-19 pandemic occurred in several waves with different levels of seriousness. Healthcare personnel (HCP) constituted a high-risk population for COVID-19, necessitating monitoring of their knowledge, attitudes, and practices (KAP) status and level of psychological distress. This study investigated differences in the impacts of COVID-19 during and after the Omicron outbreak among HCP in Indonesia.Methods: An online structured questionnaire survey was distributed twice in selected hospitals of Indonesia: the first survey was between December 2021 and February 2022 (Omicron era) and the second between August and October 2022 (post-Omicron era). A multiple logistic regression model was used to determine the differences in KAP and psychological distress among HCP toward COVID-19 by adjusting the demographic characteristics. This is a provisional file, not the final typeset article Results: This study included 402 (Omicron era) and 584 (post-Omicron era) HCP members. Positive attitudes were more common in the Omicron era than in the post-Omicron era (p = 0.001). The availability of face shields and protective eyewear significantly decreased from 62.7% to 55.6% (p = 0.028). However, psychological distress among HCP significantly increased after the Omicron outbreak (p = 0.024). Multiple logistic regression analyses revealed a decrease of positive attitudes (OR = 0.626; 95% CI = 0.476-0.823) in the post-Omicron era.Our data indicated a significant increase in psychological distress among HCP in the post-Omicron era. These findings suggest a need for greater focus on psychological distress among HCP in Indonesia.